Peptide microarray‐based analysis of antibody responses to SARS‐CoV‐2 identifies unique epitopes with potential for diagnostic test development. Issue 7 (7th May 2021) - Holenya, Pavlo; Lange, Paul Joris; Reimer, Ulf; Woltersdorf, Wolfram; Panterodt, Thomas; Glas, Michael; Wasner, Mark; Eckey, Maren; Drosch, Michael; Hollidt, Jörg‐Michael; Naumann, Michael; Kern, Florian; et al.
Abstract: Humoral immunity to the Severe Adult Respiratory Syndrome (SARS) Coronavirus (CoV)‐2 is not fully understood yet but is a crucial factor of immune protection. The possibility of antibody cross‐reactivity between SARS‐CoV‐2 and other human coronaviruses (HCoVs) would have important implications for immune protection but also for the development of specific diagnostic ELISA tests. Using peptide microarrays, n = 24 patient samples and n = 12 control samples were screened for antibodies against the entire SARS‐CoV‐2 proteome as well as the Spike (S), Nucleocapsid (N), VME1 (V), R1ab, and Protein 3a (AP3A) of the HCoV strains SARS, MERS, OC43, and 229E. While widespread cross‐reactivity was revealed across several immunodominant regions of S and N, IgG binding to several SARS‐CoV‐2‐derived peptides provided statistically significant discrimination between COVID‐19 patients and controls. Selected target peptides may serve as capture antigens for future, highly COVID‐19‐specific diagnostic antibody tests. Abstract : SARS‐CoV‐2 whole‐proteome peptide microarray analysis of antibody reactivity in Covid‐19 patient sera revealed several epitopes and confirmed the presence of humoral cross‐reactivity between SARS‐CoV‐2 and ubiquitous "common cold" human coronaviruses. The identified epitopes may provide the basis for the development of a specific and sensitive diagnostic test.